Obesity and endoplasmic reticulum (ER) stresses - Tripathi, Yamini B.; Pandey, Vivek (Frontiers in Immunology, 2012)
In obesity, the adipose cells behave as inflammatory source and result to low grade inflammation. This systemic inflammation along with oxidative stress is a silent killer and damages other vital organs also. High metabolic process, induced due to high nutritional intake, results to endoplasmic reticulum (ER) stress and mitochondrial stress. This review describes the triggering factor and basic mechanism behind the obesity mediated these stresses in relation to inflammation. Efforts have been made to describe the effect- response cycle between adipocytes and non-adipocyte cells with reference to metabolic syndrome.